Spectrum and prevalence of renal dysfunction among heart failure patients attending tertiary care hospital: first report from Somalia - Mohamed Osman Omar Jeele; Ahmed Abdirahman Hussein; Mohamed Abdullahi Mohamud; Abdulkamil Abdullahi Adani; Mohamed Farah Yusuf Mohamud (SpringerOpen, 2023)
Abstract Introduction Heart failure is one of the major global health problems that we face today, worldwide. The main objective of our study is to evaluate the spectrum and prevalence of renal dysfunction among heart failure patients in Mogadishu, Somalia. The design of the study is a retrospective descriptive study aimed at heart failure patients who presented to the largest tertiary care center in southern somalia between January 2021 to september 2021. Demographic data, co-morbidities, types of heart failure, causes of heart failure and the presence or absence of renal dysfunction were analysed. Results Overall 180 heart failure patients were enrolled in the study. The mean age of the participants was 62.26 ± 14 years. Regarding the age group, patients aged between 61-80 years was the most abundant participants with (n = 87, 48.3%). Regarding the type of heart failure in our study, HFpEF was the most common type in our respondents with frequency of (n = 85, 47.2%). When analysed the cause of heart failure among patients; hypertension was the most common cause of heart failure (n = 90, 50%). Also, hypertension was the most common co-morbidity among our patients (n = 106, 59%), followed by coronary artery diseases (n = 50, 28%). The prevalence of renal dysfunction in heart failure patients was (n = 37, 20.6%). Our analysis showed that among the 37 renal dysfunction patients, 12.3% of them (n = 22) were CKD (chronic kidney disease) while the remaining 8.3% (n = 15) had AKI (acute kidney injury). We found a significant correlation between gender and renal dysfunction in heart failure patients with (95% CI: 0.098-0.574, OR: 0.237, p value: < 0.001). Males were 2 and half times more likely to develop renal failure than females. Conclusions we found that the prevalence of renal dysfunction in heart failure patients is 20.6%. It was more prevalent in males and elderly population.